IMPLEMENTATION OF LEARNING MANAGEMENT AT DARUL AMAN ISLAMIC BOARDING SCHOOL OF ACEH BESAR DISTRICT - Miswar, Miswar (PT. Antis International Publisher, 2024)
Some teachers will complete the learning tool when there is a visit by the school supervisor to the pesantren and also when they complete it only to complete the requirements to receive the teacher's professional allowance. The results of the study are (1). The planning implications in the learning management at Darul Aman Islamic Boarding School of Aceh Besar District are proven by holding a teaching plan, because teaching planning is a very important matter arranged optimally before the learning process is implemented, whether or not the learning process is carried out out well depending on the teaching plan that has been set together. Islamic Boarding School leaders as supervisors are able to guide and supervise teachers in preparing teaching plans. (2). The implementation implications in the learning management at Darul Aman Islamic Boarding School Of Aceh Besar District is the learning process is carried out with a). Manage the learning process, b). Manage classes, c). Using media, d). Mastery of the educational foundation, and e). Manage learning interactions. (3). The implications of controlling in the learning management at Darul Aman Islamic Boarding School of Aceh Besar District are carried out by evaluating the weaknesses and programs that have been implemented to improve the implementation of the program to improve future learning. Control is carried out in the provision of reports carried out and discussed together